Issues faced by small owner-managed enterprises / Wang Wei and Ameen Talib - Wang, Wei; Talib, Ameen (Universiti Teknologi MARA, Shah Alam: Malaysian Academy of SME and Entrepreneurship Development (MASMED), 2019)
This paper explores the issues confronted by small owner-managed enterprises (SOME) in Singapore. The methodology adopted was in-depth interviews of four owner managers. The interviews were conducted in an exploratory fashion; without any pre-conceived ideas or hypothesis. The interviewees were asked to talk about their business and the main challenges they face. The findings from the interviews indicate that manpower issues, regulations and securing funding were the main issues. We also interviewed a SME centre manager to validate/collaborate the owner-managers interviews.